2019
DOI: 10.1186/s12917-019-2131-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma β-hydroxybutyric acid and conjugated linoleic acid in milk as a biomarker for early diagnosis of ketosis in postpartum Polish Holstein-Friesian cows

Abstract: BackgroundThe aim of this study was to investigate the association between plasma β-hydroxybutyric acid (BHBA) and conjugated linoleic acid in postpartum Polish Holstein-Friesian (PHF) cows. The experiment was carried out at an experimental dairy farm, where a herd of approximately 350 cows was kept. Samples were taken at six time points: between days 5–7, 8–14, 15–21, 22–28, 29–35, and 36–42, resulting in 510 samples of both milk and blood. The cows involved in the experiment were divided into two groups – ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Buttchereit et al [ 30 ] also showed that strong mobilization of energy from lipid tissue is not only conducive to more intensive production of long-chain FAs, but can also reduce the protein content in milk. This is consistent with the tendency observed by Pupel et al [ 31 ] and with our results regarding levels of κ–casein. Our results for the content of the main FA fractions are in agreement with those reported by Petit and Côrtes [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Buttchereit et al [ 30 ] also showed that strong mobilization of energy from lipid tissue is not only conducive to more intensive production of long-chain FAs, but can also reduce the protein content in milk. This is consistent with the tendency observed by Pupel et al [ 31 ] and with our results regarding levels of κ–casein. Our results for the content of the main FA fractions are in agreement with those reported by Petit and Côrtes [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…The cows in this group, however, had the lowest glucose level in the blood, which in our study was negatively correlated with NEFA (−0.386, p ≤ 0.05). Puppel et al [ 31 ] showed very strong negative correlations between the BHBA level in the blood and the content of CLA–9 and –10. Our results are consistent with those reported by Vanbergue et al [ 26 ], who studied the milk of Holstein and Normande cows up to the peak of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The main FAs deposited in the adipocytes are C16:0, C16:1, C18:0 and C18:1 [ 26 ]. Indeed, during lipolysis, induced by NEB, there is a particular increase in the bloodstream of the C16:0, C18:0 and C18: 1 and Linoleic acids (C18: 2) [ 26 , 38 ]. As previously reported, the plasma acidic profile reflects the fatty acid composition of the fat reserves [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HK the trend of concentration of the FA is variable from one to the other indeed, the C18:1 ω 9 is a biomarker of a state of hyperketonaemia when it exceeds the cut-off. Furthermore, high milk concentration of C18:1 ω 9 could be used as biomarker for diagnosis of high blood concentration of NEFA and BHB in early phase of lactation [ 38 , 57 ]. Concentrations of Oleic acid equal to or greater than 24 g per 100 g of milk indicate the presence of blood NEFA greater than 0.6 mmol/L [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation